Machining of ultralight magnesium alloy AZ31 - Wong, Benjamin Yu Zhi. (2012)
Magnesium (Mg) and its alloys are widely used as structural material in many industries because of its low density (and lightweight properties), good machinability and high specific strength as well as recyclability. Even though magnesium alloys are popularly produced into cast parts or wrought products, some form of machining operations are still required.